Use of the chronic illness research recruitment taxonomy to evaluate recruitment strategies in an eHealth feasibility study. - Rosalynn C. Austin; Anne Marie Lunde Husebø; Hege Wathne; Marianne Storm; Kristin H. Urstad; Ingvild Morken; Bjørg Karlsen (Contemporary Clinical Trials Communications)
Background: Chronic illness research has many challenges making research recruitment difficult. Despite reports of facilitators and barriers to research recruitment challenges remain. The reporting of research strategies and their impact on recruitment and subsequent randomised control trials is not sufficient. A newly developed chronic illness research recruitment taxonomy (CIRRT) details factors and elements observed to impact recruitment around the components of Project, People, and Place. This paper aims to use the chronic illness research recruitment taxonomy to report and evaluate the recruitment strategies, impact they had on recruitment, and alterations to an eHealth feasibility study. Methods: Retrospective mixed method approach was used to inductively code the research team meeting minutes during the recruitment period. The coding was then abductively matched to the chronic illness research recruitment taxonomy and gaps in the CIRRT noted. Dated coding data were integrated with recruitment progress to explore the impact of research recruitment strategies. Results: Meeting minutes (n = 66) were analysed, recruitment strategies identified and matched to CIRRT. The reporting and identification of the recruitment strategies was aided by CIRRT use. By integrating the codes that aligned with CIRRT with recruitment progress was observed to be impacted by staffing and researcher visits. Conclusions: CIRRT may be a useful tool in the evaluation and reporting of research recruitment strategies. Altering the roles of nurses involved and researcher visits to recruiting sites may positively impact on chronic illness research recruitment.